Addressing Human Vulnerability to Climate Change : Toward a 'No-Regrets' Approach - Heltberg, R. (2012)
This paper presents and applies a conceptual framework to address human vulnerability to climate change. Drawing upon social risk management and asset-based approaches, the conceptual framework provides a unifying lens to examine links between risks, adaptation, and vulnerability. The result is an integrated approach to increase the capacity of society to manage climate risks with a view to reduce the vulnerability of households and maintain or increase the opportunities for sustainable development. We identify 'no-regrets' adaptation interventions, meaning actions that generate net social benefits under all future scenarios of climate change and impacts. We also make the case for greater support for community-based adaptation and social protection and propose a research agenda. (C) 2008 Elsevier Ltd. All rights reserved.